Cultivation of Students' Spiritual Awareness Through the Integration of PAI Learning and Extra-Curricular Activities at Senior High School (SMAN) 2 Teluk Kuantan, Kuantan Singingi - Alhairi, Alhairi; Akbar, Helbi; Lasmiadi, Lasmiadi; Andrizal, Andrizal (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
The spiritual building is an effort to carry out mental or spiritual refreshment in the form of belief, faith, ideology, ethics, guidelines and guidance. Spiritual development can be done using various media, one of which comes from religion, which is called